Information Technology - New Generations 15th International Conference on Information Technology (Advances in Intelligent Systems and Computing,, 2018)
This volume presents a collection of peer-reviewed, scientific articles from the 15th International Conference on Information Technology - New Generations, held at Las Vegas. The collection addresses critical areas of Machine Learning, Networking and Wireless Communications, Cybersecurity, Data Mining, Software Engineering, High Performance Computing Architectures, Computer Vision, Health, Bioinformatics, and Education. Features the most recent advances in information technology; Presents early work and novel results from research laboratories around the world; Facilitates managers making business decisions, academics shaping research work, and educators keeping abreast of recent advances in learning technologies.